Management of Urban Transport Services Financing in Bekasi City 2018-2022 - Aulia, Daffa Bahy Putra; Lutfi, Achmad (Journal Public Policy, 2024)
The aims of this study are to analyze the management of Trans Patriot urban service financing in Bekasi City from 2018 to 2022. Using Olander’s Public Finance Management (PFM) theory, the research focuses on six dimensions: strategic planning, budget preparation, budget execution, accounting and monitoring, reporting and audit, and policy review. A post-positivist approach is employed, with data collected through in-depth interviews with six informants and a literature study, followed by qualitative data analysis. The results indicate several issues: uncertainty in budget execution, a heavy reliance on subsidies and capital participation, and a lack of transparency in financial reporting and auditing. Specifically, problems with policy communication among stakeholders and non-compliance with Government Regulation No. 12 of 2019 and Minister of Home Affairs Regulation No. 77 of 2020 were identified. The study concludes that the Bekasi City Government needs to resolve policy uncertainty, diversify funding sources, and enhance transparency and accountability through comprehensive audits and reporting mechanisms like LKPD and LK BUMD. Regular policy evaluations of Trans Patriot's financial management are also recommended. Despite limitations in data sources, the research underscores the urgency for better financial governance to ensure the sustainability of public transportation services in Bekasi.